1995
DOI: 10.1128/aem.61.8.3069-3075.1995
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative fluorescence in situ hybridization of Bifidobacterium spp. with genus-specific 16S rRNA-targeted probes and its application in fecal samples

Abstract: Three 16S rRNA hybridization probes were developed and tested for genus-specific detection of Bifidobacterium species in the human fecal flora. Variable regions V2, V4, and V8 of the 16S rRNA contained sequences unique to this genus and proved applicable as target sites for oligodeoxynucleotide probes. Determination of the genus specificity of the oligonucleotides was performed by whole-cell hybridization with fluorescein isothiocyanate-labelled probes. To this end, cells were fixed on glass slides, hybridized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
357
0
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 889 publications
(370 citation statements)
references
References 35 publications
10
357
0
3
Order By: Relevance
“…This suggests that these allelic probes were reporting on distinct subpopulations of the bacterial group, and thus neither is reporting on the entire group present at any one time. Regarding absolute coverage, as noted above, the two direct quantification methods report maximum values within one (slot blots) or one-half (qPCR) order of magnitude of the 10 11 bacteria per gram of feces reported by microscopy and fluorescence in situ hybridization (Langendijk et al, 1995;Franks et al, 1998;Suau et al, 1999;Harmsen et al, 2002). We consider this a rather good agreement, given the previously documented diversity of targets in fecal specimens.…”
Section: The Animals and Their Bacteriasupporting
confidence: 65%
“…This suggests that these allelic probes were reporting on distinct subpopulations of the bacterial group, and thus neither is reporting on the entire group present at any one time. Regarding absolute coverage, as noted above, the two direct quantification methods report maximum values within one (slot blots) or one-half (qPCR) order of magnitude of the 10 11 bacteria per gram of feces reported by microscopy and fluorescence in situ hybridization (Langendijk et al, 1995;Franks et al, 1998;Suau et al, 1999;Harmsen et al, 2002). We consider this a rather good agreement, given the previously documented diversity of targets in fecal specimens.…”
Section: The Animals and Their Bacteriasupporting
confidence: 65%
“…Previous studies that have attempted to quantitate bacterial populations in faecal material, or in in vitro model systems, have usually employed classical culturing techniques, with varying levels of success (Moore & Holdeman, 1974;Macfarlane & Macfarlane, 1997;Suau et al, 1999;Harmsen et al, 2000a). Fastidious nutritional requirements, or the need for a particular syntrophic species for growth can prevent accurate enumeration of some types of bacteria in the gut (Langendijk et al, 1995;Harmsen et al, 2000a) and this has stimulated development of a variety of molecular techniques that obviate the need for culture (Amann et al, 1995;Zoetendal et al, 1998). Fluorescence in situ hybridization (FISH) has been used to enumerate bacteria in faeces and it has been reported that approximately 80% of the resident microflora has been categorized (Franks et al, 1998;Harmsen et al, 2000a).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding and predicting the e¡ects of dietary change, stress, exercise, age, drug treatment or disease upon the complex microbial ecosystem of the gut requires both a basic knowledge of the composition of the micro£ora and a rapid and convenient technique for their study. Culture-based methods are often laborious, time consuming and may recover only a small fraction of the total microbial diversity present within the gut [17]. Molecular methods based on PCR have the advantage of producing direct information on community structure and provide an e¤cient strategy for describing microbial biodiversity within environmental samples [13,18^20].…”
Section: Introductionmentioning
confidence: 99%